A avaliação do programa criança feliz na perspectiva do beneficiário - Denardin, Adriele Carine Menezes (2022)
The integral development in early childhood is essential for the formation of the individual. The attention and care policies in this period not only allow full development in the first years of life, but also aim to end a cycle of poverty that these individuals find themselves in, providing a better economic and social future for a country. In this sense, in Brazil, public policies aimed at child development have been gradually gaining ground as legislation on the subject has been strengthened over the years. The Criança Feliz Program (PCF), created in 2016, with the objective of strengthening the development of early childhood in Brazil through home visits, seeks to serve individuals in a situation of socioeconomic vulnerability, its beneficiaries include pregnant women and children up to 3 years of age enrolled in Bolsa Família, and children up to 6 years of age who are part of the beneficiaries of the Benefício de Prestação Continuada (BPC) from the Federal Government. Recognizing the importance of this social program, and its possible impact on the life of Brazilians who live in an unfavorable economic and social situation, the present work, of a qualitative nature, seeks through a script of interviews to evaluate the perception of the results of the Criança Feliz Program. from the perspective of its beneficiaries. In order to fulfill the objective of evaluating the PCF, the present study is inclined to evaluate the quality of the services provided. In this sense, it is understood that the user must be the central element in the evaluation of the quality of services, regardless of their nature, because of this, this research was developed with 78 PCF beneficiaries from 5 municipalities in Rio Grande do Sul. The results of the study suggest that the PCF has been presented as an important tool for the development of children whose family members participated in the research, in addition, the families surveyed positively evaluated the dimensions presented by the adapted model of the tool that evaluates the quality of services. However, it should be noted that intersectoriality, one of the pillars of the program, proved to be fragile in the context of this research insofar as few interventions were mentioned in which there was any articulation between the PCF and the service networks of the municipalities.